Biographical and autobiographical writings - Alberti, Leon Battista 1404-1472 (The I Tatti Renaissance library, 2023)
"Leon Battista Alberti (1404-1472) was one of the most famous figures of the Italian Renaissance. His extraordinary range of abilities as a writer, architect, art theorist, and even athlete earned him the title of the first "Renaissance man." Alberti was a prolific author, but only a few of his works are well known today: these are his vernacular dialogue on the family (De familia, 1433-43); his treatise on painting, which he wrote first in the vernacular and then in Latin (Della pittura/De pictura, 1435-36; 1439-41); and his Latin treatise on architecture, De re aedificatoria (On the Art of Building), written 1443-72. Yet these represent only the tip of the huge iceberg of writings that he composed.